2015
DOI: 10.1212/wnl.0000000000001780
|View full text |Cite
|
Sign up to set email alerts
|

ABCD2 score and secondary stroke prevention

Abstract: Editorial, page 304Supplemental data at Neurology.org ABCD2 score and secondary stroke prevention Meta-analysis and effect per 1,000 patients triaged ABSTRACT Objective: Patients with TIA have high risk of recurrent stroke and require rapid assessment and treatment. The ABCD2 clinical risk prediction score is recommended for patient triage by stroke risk, but its ability to stratify by known risk factors and effect on clinic workload are unknown.Methods: We performed a systematic review and meta-analysis of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 55 publications
2
66
0
2
Order By: Relevance
“…Despite some encouraging reports regarding this score [9], it is difficult to see how to use it in clinical practice, as all patients who have had a TIA need a prompt investigation. Recent meta-analyses found its discriminative value to be low, and that it led to only small revisions in the baseline stroke risk [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite some encouraging reports regarding this score [9], it is difficult to see how to use it in clinical practice, as all patients who have had a TIA need a prompt investigation. Recent meta-analyses found its discriminative value to be low, and that it led to only small revisions in the baseline stroke risk [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Some patients who are classified as having low risk on the ABCD 2 score may have important potentially treatable TIA etiologies, such as symptomatic carotid artery stenosis or atrial fibrillation, that require urgent treatment. 23 These limitations have prevented widespread adoption of the ABCD 2 score to triage patients with TIA. 24 The Rotterdam Study 25 followed patients with transient neurologic attacks for 10 years and found an increased risk of stroke not only in patients with focal symptoms (ie, possible TIAs) but also in patients who had transient episodes of nonspecific symptoms.…”
Section: Prognosismentioning
confidence: 99%
“…69 Moreover, recent studies have challenged the value of the ABCD 2 score for predicting stroke recurrence risk. 10 However, the ABCD 2 score and more recent scores are limited by their derivation from mostly nonneurologist-diagnosed TIA samples and by their development before the 2009 American Heart Association–endorsed TIA definition, which takes into account the presence of infarct on neuroimaging. 11 Prediction scores have not been frequently applied to minor stroke, 9 which may carry the same or higher risk of early recurrent stroke as TIA.…”
mentioning
confidence: 99%